Pembinaan Sumber Daya Manusia Kesehatan Tentang Raja Damai Lahir di Tengah Kegelisahan di RS UKRIDA Jakarta - Amirrudin Zalukhu (Pusat Riset dan Inovasi Nasional, 2025)
This Community Service Program was motivated by the urgent need for inner peace and spiritual reinforcement among healthcare workers operating under the high-pressure demands of modern medical settings. Through the theme “The Prince of Peace Is Born Amidst Restlessness,” this program explored the theological message of Luke 2:1–20 to reflect on the presence of Christ’s peace in the midst of worldly chaos. The primary objective of the activity was to provide a spiritually restorative understanding that inspires renewed commitment to compassionate and meaningful service. The program was conducted in the form of a spiritual lecture and guided personal reflection, involving healthcare professionals of various disciplines at UKRIDA Hospital. The results indicated strong positive responses from participants who found the message of Christmas to be deeply relevant to their professional context. Participants expressed new spiritual awareness and initial commitments to embody peace in their workplace interactions. The evaluation highlighted both the impact and the need for regular spiritual formation programs integrated into the hospital's work culture. This initiative underscores the importance of integrating professionalism with Christian spirituality to cultivate a healthier and more meaningful work environment.